Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12875-022-01766-z
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic solutions to enhance self-management skills in solid organ transplant patients: systematic review and thematic analysis

Abstract: Background In organ transplantation, all patients must follow a complex treatment regimen for the rest of their lives. Hence, patients play an active role in the continuity of the care process in the form of self-management tasks. Thus, the main objective of our study was to investigate the pragmatic solutions applied by different studies to enhance adherence to self-management behaviors. Method A systematic review was conducted in five databases f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…8 9 The adoption of telemedicine services in other solid organ transplant care has shown the great potential of telehealth technology to improve the healthcare delivery model by providing increased patient-to-healthcare team interactions and accessibility. [8][9][10][11][12][13] Such programmes engage transplant patients in their self-management activities and enhance the doctorpatient relationship.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…8 9 The adoption of telemedicine services in other solid organ transplant care has shown the great potential of telehealth technology to improve the healthcare delivery model by providing increased patient-to-healthcare team interactions and accessibility. [8][9][10][11][12][13] Such programmes engage transplant patients in their self-management activities and enhance the doctorpatient relationship.…”
Section: Open Accessmentioning
confidence: 99%
“…Evidence showed that supporting transplant patients with additional technology-based support care programmes alongside traditional care could provide real-time patient access to the transplant team and emergency medical services 8 9. The adoption of telemedicine services in other solid organ transplant care has shown the great potential of telehealth technology to improve the healthcare delivery model by providing increased patient-to-healthcare team interactions and accessibility 8–13. Such programmes engage transplant patients in their self-management activities and enhance the doctor–patient relationship.…”
Section: Introductionmentioning
confidence: 99%
“…For SOTx patients, absence or insufficient attention to self-management can result in such complications [ 4 ]. Typically, patients need to monitor signs of infection, medication side-effects, and physical and psychological status and implement healthy lifestyle changes (such as a special diet, psychosocial problems, mental health problems, and substance use) [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. In terms of a medication regimen, patients must learn how to calculate dosages of interacting medications.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence of an association between self‐management behaviors and improved health outcomes in adults, such as physical activity post‐transplant, 10 and interventions aimed at improving self‐management behaviors are considered ‘crucial for better outcomes’ 11 . However, an increasing body of research into adolescent patients, including those of other chronic illness populations in which a high level of self‐management is required, for example HIV and diabetes, 12,13 indicates that taking on more responsibility for such tasks is associated with poorer outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…9 There is evidence of an association between self-management behaviors and improved health outcomes in adults, such as physical activity post-transplant, 10 and interventions aimed at improving self-management behaviors are considered 'crucial for better outcomes'. 11 However, an increasing body of research into adolescent patients, including those of other chronic illness populations in which a high level of self-management is required, for example HIV and diabetes, 12,13 indicates that taking on more responsibility for such tasks is associated with poorer outcomes. In organ transplant recipients, Fredericks et al 14 found an increase in perceived selfmanagement skills and regimen knowledge with chronological age, but the association between age and performance on the domain assessing these skills did not reach statistical significance.…”
mentioning
confidence: 99%